Sitting bucks: Stale pricing in fixed income funds - Choi, Jaewon; Kronlund, Mathias; Oh, Ji Yeol Jimmy (Journal of Financial Economics, 2022)
We find evidence of widespread stale pricing in bond mutual funds and the resulting risks of dilution and fragility. A principal driver of this phenomenon is the high illiquidity of funds’ holdings, which makes accurate pricing difficult and provides funds with greater discretion over valuation. Consequently, net asset values (NAVs) are extremely stale and fund returns are predictable over several days and weeks, particularly during market crises. Opportunistic traders withdraw capital from overvalued funds, exacerbating the risk of fund runs, while buy-and-hold investors face annual dilution of around $1.2 billion. Our results highlight adverse consequences of insufficient fair valuation practices that remain pervasive even after corrective regulations that followed the 2003 market-timing scandal.